(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the effectiveness of innovative pedagogical approaches for students with special educational needs. It provides information on measures to enhance students’ creative abilities in the learning process through teaching methods developed based on modern technologies and specialized methodologies. The study explores ways to help students with special educational needs acquire knowledge more effectively and adapt better to social environments. Additionally, the article analyzes the impact of adapted curricula and ICT tools on the learning process and investigates ways to improve the effectiveness of education through specialized integrative approaches.